Gideon Falls. Book 2. Original sins - Lemire, Jeff (Image Comics, 2019)
The mystery deepens... As the reclusive and troubled young man Norton becomes more immersed in his quest for the secret of the legendary Black Barn, washed-up Catholic priest Father Fred unravels the secret behind a series of grisly murders."--Provided by publisher.